Bridge or Barrier? How Digital Competence Predicts Student Attitudes Toward Generative AI Ethics and Usage - Astrero, Mark Kevin (Research and Advances in Education, 2026)
With the rapid rise of Generative Artificial Intelligence (GenAI), it is important to examine how GenAI, digital competency, and ethics intersect. The Philippines has few studies that analyze these three categories together; this study seeks to understand better how they interact. It used Structural Equation Modelling to conduct a quantitative correlational investigation on this topic. Stratified random sampling was used to poll 498 college students from diverse institutions in Isabela, Philippines, to ensure demographic and intellectual diversity. Students’ digital competencies, GenAI adoption, and ethical concerns were assessed via an online questionnaire. The study found that students exhibited high digital competence (M = 3.48) and a moderate desire to employ Generative AI (M = 3.24), but moderate ethical concerns (M = 3.15). Males were more willing to use GenAI than females (p = 0.011), and fourth-year students exhibited greater ethical concerns and a greater willingness than first-year students. The regression study showed that willingness to use and moral concerns explained 33.2% of the variance in digital competence. Overall, students are technically ready to use GenAI, but their digital competence and ethical application of it remain lacking. Higher education institutions should offer comprehensive professional development and an inclusive curriculum that integrates technical instruction with a strong moral foundation. The gender gap and changing requirements of students at different year levels should be the focus of these activities.